Multi Directional Repeated Sprint Is a Valid and Reliable Test for Assessment of Junior Handball Players - Daneshfar, Amin; Gahreman, Daniel E.; Koozehchian, Majid S.; Amani Shalamzari, Sadegh; Hassanzadeh Sablouei, Mozhgan; Rosemann, Thomas; Knechtle, Beat; Nikolaidis, Pantelis T. (Frontiers in Physiology, 2018)
The aim of the present study was to examine the validity and reliability of a 10×(6×5m) multi-directional repeated sprint ability test (RSM) in elite young team handball (TH) players. Participants were members of the Iranian national team (n=20, age 16.4±0.7 years, weight 82.5±5.5kg, height 184.8±4.6cm, body fat 15.4±4.3%). The validity of RSM was tested against a 10×(15+15m) repeated sprint ability test (RSA), Yo-Yo Intermittent Recovery test Level 1 (Yo-Yo IR1), squat jump (SJ) and countermovement jump (CMJ). To test the reliability of RSM, the participants repeated the testing sessions of RSM and RSA one week later. Both RSA and RSM tests showed good to excellent reliability of the total time (TT), best time (BT), and weakest time (WT). The results of the correlation analysis showed significant inverse correlations between maximum aerobic capacity and TT in RSA (r=- 0.57, p≤0.05) and RSM (r=-0.76, p≤0.01). There was also a significant inverse correlation between maximum aerobic capacity with fatigue index (FI) in RSA test (r=-0.64, p≤0.01) and in RSM test (r=-0.53, p≤0.05). BT, WT and TT of RSA was largely-to-very largely correlated with BT (r=0.58, p≤0.01), WT (r=0.62, p≤0.01), and TT (r=0.65, p≤0.01) of RSM. BT in RSM was also correlated with FI in RSM (r= 0.88, p≤0.01). In conclusion, based on the findings of the current study, the recently developed RSM test is a valid and reliable test and should be utilised for assessment of repeated sprint ability in handball players.